College Students Media Multitasking Behavior - Maria Margaretha Kedjo; M.Dinah Ch Lerik; R.Pasifikus Christa Wijaya (Journal of Health and Behavioral Science, 2020)
Activities involving the use of several media simultaneously or alternately while working on a task are even better known as multitasking behavior in using media (media multitasking). This study aims to describe the behavior of multitasking in using media for students at the University of Nusa Cendana (Undana). The approach used is a quantitative approach with a descriptive research type. The data collection technique used the MMM-S Likert scale with the results of the measuring instrument trial showing the Cronbach alpha scale value of 0.856. The research respondents were 395 Undana students. The results of the study found that Undana students showed high multitasking behavior in using media because the empirical mean was greater than the hypothetical mean (40.17> 30), with a low category of 39 people, medium 132 people, and high as many as 224 people. Multitasking behavior in using the media is known to be 4.24 times more women respondents than men, in the age range 22-25 years, 1.64 times more than those aged 18-21 years, while based on where the respondents live in 1.32 times more households than living in a boarding house.